A randomized, double-blind, phase 2 study evaluating the safety and efficacy of AMG 416 for the treatment of secondary hyperparathyroidism in hemodialysis patients. (May 2015) - Bell, Gregory; Huang, Saling; Martin, Kevin J.; Block, Geoffrey A.
Abstract Objective: Secondary hyperparathyroidism (SHPT) is a frequent complication of chronic kidney disease. We evaluated AMG 416, a long-acting peptide agonist of the calcium-sensing receptor, to assess its safety, tolerability, and efficacy and to determine a safe and effective starting dose for subsequent phase 2 studies. The study was not designed to titrate AMG 416 dosing to achieve a specific PTH treatment goal. Research design and methods: This is a multicenter, double-blind, randomized, placebo-controlled, dose-escalation study designed to evaluate the safety and efficacy of AMG 416 administered thrice weekly by IV bolus at the end of hemodialysis for up to 4 weeks. Eligible subjects were enrolled in one of three cohorts and treated with 5 mg of AMG 416 or placebo for 2 weeks (Cohort 1) or 5 or 10 mg of AMG 416 or placebo for 4 weeks (Cohorts 2 and 3). The primary endpoint was mean percentage change from baseline in PTH during the efficacy assessment phase (EAP) in Cohorts 2 and 3. Results: Analysis of the primary endpoint showed that treatment with AMG 416 at 10 mg (Cohort 2) and 5 mg (Cohort 3) for up to 4 weeks resulted in mean 49.4% and 33.0% reductions from baseline in PTH during the efficacy assessment phase, respectively (p < 0.05 for both cohorts compared to placebo group within the cohort). A substantial proportion of subjects treated with AMG 416 achieved PTH ≤300 pg/mL and ≥30% reduction in PTH from baseline in both cohorts. The observed decreases in serum-corrected calcium were well tolerated and serum phosphate levels also tended to decrease. Conclusions: The present clinical findings support the continued development of AMG 416 as a treatment for SHPT in hemodialysis patients.